Monarchical Political Culture as a Negotiation Mechanism: The Sultan’s Authority and the Control of Protest Dynamics in Yogyakarta - Wahyu Kuncoro (Journal of Politics and Policy, 2025)
This study examines how local wisdom operates as a mechanism of political negotiation to reduce anarchic tendencies in protests in Yogyakarta, Indonesia. The research focuses on the dynamics of demonstrations, a period marked by heightened student activism and public dissent in various Indonesian cities. Unlike other regions where protests often escalate into repressive or violent acts, Yogyakarta exhibits a distinctive pattern through a more dialogical and culturally grounded approach. Using a descriptive qualitative method, this study collected data through in-depth interviews, observations, and document analysis on protest dynamics and local governance practices. The findings reveal that local wisdom—embodied in the values of deliberation, social harmony, and the symbolic authority of the Sultanate—functions as a soft instrument of political negotiation among local authorities, student movements, and the broader community. This mechanism effectively mitigates conflict escalation and sustains peaceful demonstrations. This study contributes to the theory of hybrid governance by illustrating how cultural legitimacy operates as a subtle form of political negotiation within contemporary democratic practice